Selective area epitaxy of n+-GaN layers on SiO2 patterned GaN/c-Al2O3 templates by PA MBE. (December 2019) - Shubina, K Yu; Mizerov, A M; Timoshnev, S N; Mokhov, D V; Nikitina, E V; Kim, I; Bouravleuv, A D
Abstract: The n + -GaN epilayers were synthesised by PA MBE on the SiO2 patterned GaN/c-Al2 O3 templates, grown by MOCVD. Formation of the polycrystalline GaN atop of the SiO2 mask during PA MBE was observed. It was found that macroscopic voids at the interface polycrystalline GaN/SiO2 /n-GaN template appeared during the PA MBE process. The polycrystalline GaN film was completely removed by etching in hot aqueous KOH solution. Hall measurements have shown that the value of electron concentration in n + -GaN contact layer is about ne ∼4.6×10 19 cm -3 .